Organisationskulturen ur de anställdas perspektiv - Larsson, Mari (2011)
The aim of this thesis was to examine and chart the organizational culture in the Social-Services at Luleå Municipality from the employee’s perspective. Earlier research describes how an organization consists of both open and more hidden values. The open values consist of an organization’s purpose, policy, and goal and mission, while the hidden values determine how the organization works in practice, e.g. how the declared open values and policies are applied. The questions raised were: What attitudes and values have the employees to their work and how do the employees experience their role in the existing organization. By using semi-structured interviews three supervisors and six employees were asked questions about manner, lucidity, availability, engagement, responsibility, and competence. The results showed that the employee’s values were almost consistent with the Social-Services’ control-documents and policies and that they constantly discussed value-issues out in the operations to work with a common attitude and approach to, in primary, the customers. The employees emphasized certain personality traits to be more important in their profession than others, namely enjoy working with people, have a good manner, and to be humble, positive, calm, and secure. Validerat; 20111026 (anonymous)